The influence of game-based learning on tactical awareness and skill development in golf training programs - Chenghui Jin (PLoS ONE, 2025)
Objective To investigate the effects of game-based learning on tactical awareness and skill development in golf training programs. Methods A randomized controlled trial was conducted with 45 male athletes aged 18–30, divided into three groups: Tactical Awareness Training Group (TATG), Skill-Based Training Group (SBTG), and an Active Control Group (ACG). The intervention lasted eight weeks. Tactical awareness was assessed using a modified Tactical Skills Inventory for Sport (TACSIS) includes Knowing About Ball Actions (KABA), Acting in Changing Situations (ACS) and Positioning and Deciding (PD); while technical performance metrics, including Drive Distance (DD), Putting Accuracy (PA), and Swing Consistency (SC), were measured using validated tools. Pre- and post-intervention results were analyzed for within-group and between-group differences. Results Within-group improvements were significant for TATG in all tactical subscales: KABA (Δ = 15.6%, p < 0.001), ACS (Δ = 18.9%, p < 0.001), and PD (Δ = 19.2%, p < 0.001). SBTG showed significant skill improvements in DD (Δ = 3.6%, p < 0.001), PA (Δ = 7.5%, p < 0.001), and SC (Δ = −24.6%, p < 0.001). Between-group analysis indicated TATG outperformed ACG significantly on tactical awareness, and SBTG significantly outperformed ACG on technical metrics (p < 0.05). Conclusions The study highlights the complementary benefits of integrating tactical and technical training strategies in golf. Game-based learning in the TATG improved situational adaptability and strategic decision-making, while skill-focused training in the SBTG resulted in superior precision and consistency. These findings advocate for a holistic approach to golf training, incorporating both cognitive and physical components to optimize performance outcomes.